Determining Investment Priority Ratings - El Tigi, Aziz El Din (معهد التخطيط القومى, 2024)
In the previous lecture we have discussed the benefit-cost criterion in its simplest form. This lecture proceeds to shed some light on the social marginal productivity method of investment allocation as worked out by Professor H.B. Chenery. The rule however has been advocated by many economists of repute. For instance, Professor A.E. Kahn has pointed out that from the point of view of the society as a whole, the correct criterion achieving the maximum social return is the social marginal product, related to the national income as a whole. The SMP criterion has also been recommended by Profs. J. Tinbergen who has conceived the idea that priority figures generally will have to be the ratio of net results (defined as the difference between returns and total costs) to total costs, all taken at accounting prices.